1977
DOI: 10.1111/j.1528-1157.1977.tb04472.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Accumulation in Cerebral Cortical Slices: Effect of Carbamazepine, Phenobarbital, and Phenytoin

Abstract: Recent investigations have suggested that abnormal increases in brain cyclic 3',5'-adenosine monophosphate (cAMP) may play a role in epileptogenesis. Therefore, the effect of three commonly used antiepileptic drugs on cAMP accumulation in rat cortex slices was investigated. Ouabain, a depolarizing agent which produces seizures when applied to rat cortex, produced a five- to sevenfold increase in cAMP accumulation, and both carbamazepine and and phenytoin inhibited this increase. Ouabain stimulation may be medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…2). Similarly, CBZ at high concentrations also attenuates the adenosine-evoked increase in the Ievel of cyclic AMP in brain slices (Lewin and Bleck, 1977;Skenitt et al, 1983a;Weir et al, 1984), which is probably also mediated by low-affinity A 2 b-receptors (Daly et al, 1983). These effects may be at Jeast partially due to ~:-.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Similarly, CBZ at high concentrations also attenuates the adenosine-evoked increase in the Ievel of cyclic AMP in brain slices (Lewin and Bleck, 1977;Skenitt et al, 1983a;Weir et al, 1984), which is probably also mediated by low-affinity A 2 b-receptors (Daly et al, 1983). These effects may be at Jeast partially due to ~:-.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of chronic Iithium treatment on the agonist~stimulated increase in the accumulation of cyclic AMP (Belmaker, 1981;Ebstein et al, 1988) and inositol phosphates (Casebolt and Jope, 1989;Ebstein et al, 1988;Elphick et al, 1988;Godfrey et ai., 1989;Kendall and Nahors.k!, 1987) may be involved in lithium's antimanic and prophylactic properties. CBZ iru'libits the accumulation of cyclic AMP in brain slices stimulai.ed by noradrena· line, ouabain and adenosine (Lewin and Bleck, 1977;Palmer et al, 1979;Skerritt et al, 1983a;Weir et al, 1984), although only at high concentrations. CBZ's effects on the agonist-evoked formation of inositol phos-289 phates are controversial (Elphick et al, 1988: MeDermatt andLogan, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although not yet studied by many laboratories, the effects of other anti-bipolar therapeutics, such as carbamazepine, overlap at least partially with those of lithium in modulating cyclic AMP levels. [28][29][30] Since cyclic AMP can modulate transcription factors 31 which regulate the expression of many genes, stabilization by lithium of fluctuations in cyclic AMP should contribute to stabilization of the regulated genes in affected cells. Thus the bimodal model provides a framework for apparently opposing actions of lithium to be integrated into a unifying hypothesis based on minimization of the magnitude of fluctuations in signaling system activities and the consequential regulation of gene expression.…”
Section: Application Of the Model To Cyclic Ampmentioning
confidence: 99%
“…As discussed in an earlier section, evidence suggests that carbamazepine may have direct inhibitory effects on adenylate cyclase [61], and in a number of studies has been shown to attenuate stimulated cyclic AMP signaling [54,[56][57][58][59]. This finding is especially interesting noting that lithium also attenuates stimulated cyclic AMP signaling [13].…”
Section: Carbamazepinementioning
confidence: 93%
“…In addition to reports suggesting that carbamazepine effects adenosine-mediated second messenger signaling [58,234,235], the drug also appears to bind to adenosine [57,[236][237][238][239]. Carbamazepine appears to act as an antagonist, with general specificity for the A 1 subtype of adenosine receptors [57] (Table 1).…”
Section: Carbamazepinementioning
confidence: 94%